A new way of constructing the stability diagram of the system Fe–C–O with the help of a C/Fe2O3 vs. T plot and the related issue of direct and indirect reduction. (21st April 2018) - Sarkar, R.; Ghosh, D.
Abstract : A new type of Fe–C–O stability diagram, which is a plot of the molar ratio vs. temperature ( T ), is drawn for 1 atm total pressure in the temperature range 300–1300 K. Apart from delineating the stability fields of Fe and its oxides, this diagram directly furnishes the minimum number of moles of carbon required to reduce 1 mol of the starting Fe2 O3 (pure) to Fe, FeO or Fe3 O4, or their mixtures, at a given temperature and 1 atm total pressure. Besides, the confusing issue of the direct reduction (DR) vs . indirect reduction (IR) of iron oxide by carbon is reviewed and clarified, and used in the construction of the diagram. The general representations of 100 pct DR and 100 pct IR of Fe2 O3, which will be applicable at any temperature and pressure within the stability domain of Fe (solid), are proposed as follows: The combined DR and IR has the same representation as the 100 pct DR. However, in the combined case, the molar ratio CO/CO2 in the product gas is dictated by the equilibrium with Fe–FeO and in the case of 100 pct DR by the carbon saturation. For the 100 pct IR, the ratio is, again, dictated by the Fe–FeO equilibrium; in addition, the ratio C/O2 on the reactant side is governed by the carbon-saturated CO–CO2 mixture obtained from the burning of C in O2 .